UPAYA GURU BK DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK DI KELAS XI IPS SMA NEGERI 1 VII KOTO SUNGAI SARIAK KABUPATEN PADANG PARIAMAN - Winda Gustiana; Septya Suarja; Mori Dianto (Jurnal Inovasi Penelitian, 2021)
This research was motivated by the learning difficulties experienced by students at school and saw how the efforts of the counseling teachers in overcoming the learning difficulties of students. This study aims to describe the counseling teachers' efforts in overcoming the learning difficulties of students in class XI IPS at SMA Negeri 1 VII Koto Sungai Sariak. This research was conducted through a qualitative descriptive approach. This study took 3 respondents consisting of 1 key informant and 2 additional informants. The data collection method used interview techniques. Based on the results of research on the efforts of counseling teachers in overcoming learning difficulties of students in class XI IPS at SMA Negeri 1 VII Koto Sungai Sariak, namely: 1) BK teachers have good abilities in identifying learning difficulties of students. 2) BK teachers have good abilities in responding to learning difficulties of students. 3) The counseling teacher's efforts are successful in overcoming the learning difficulties of students in class XI.